Escenarios de realidad virtual gamificada y su incidencia en el fomento de la motivación del aprendizaje de la escritura en el contexto universitario - Navas Gotopo, Soratna Verónica (2025)
This research focused on determining the impact of using gamified virtual reality environments on writing skills development in university settings. The aim was to implement new teaching methods that promote meaningful learning based on digital competencies and motivation. Methodologically, the study employed Pedagogical Action Research, which involved deconstruction, reconstruction, and validation phases. The population consisted of 278 first-year students enrolled in the Language and Communication course at a private university in southern Lima. The results demonstrated the effectiveness of the implemented strategies in enhancing student motivation, primarily due to the activation of dopamine, a neurotransmitter responsible for driving action towards efficiently solving challenges. A significant finding was the promotion of autonomous learning, as the prior review of resources facilitated the resolution of challenges. Consequently, Flipped Learning effectively prepared students for hybrid classes and encouraged active apprentices. The study concludes that the use of gamified virtual reality environments positively impacts the development of students' writing skills. Motivated students showed greater willingness to practice and refine their abilities, which in turn led to an improvement in the quality of their writing.